2018
DOI: 10.1111/apt.14799
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, treatment completion and safety of sofosbuvir/ledipasvir and paritaprevir/ritonavir/ombitasvir + dasabuvir in patients with chronic kidney disease: an ERCHIVES study

Abstract: SOF/LDV and PrOD achieved high SVR rates in CKD population. Treatment completion rates were lower than expected. A decline in eGFR and development of anaemia were observed in a substantial proportion of persons, but the clinical implications remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 26 publications
3
32
2
Order By: Relevance
“…On the other hand, Saxena et al in the famous TARGET study, reported treatment discontinuation in 79/1789 (4%), half of them discontinued treatment because of adverse events; serious adverse events occurred in (6%) . Treatment completion rate of SOF‐based therapy in our study is paradoxically better than that observed with the use of renal disease specific regimens, whether it was paritaprevir/ritonavir/ombitasvir+dasabuvir±ribavirin in ERCHIVES study where only 69% (38/55) of patients with stage 4 − 5 CKD completed therapy, or grazoprevir/elbasvir in the C‐SURFER study where 6/122 patients (4.9%) were excluded from the primary efficacy analysis for non‐virological reasons . The latter were death, loss to follow‐up, non‐compliance, patient withdrawal and withdrawal by physician for violent behaviour.…”
Section: Discussioncontrasting
confidence: 63%
“…On the other hand, Saxena et al in the famous TARGET study, reported treatment discontinuation in 79/1789 (4%), half of them discontinued treatment because of adverse events; serious adverse events occurred in (6%) . Treatment completion rate of SOF‐based therapy in our study is paradoxically better than that observed with the use of renal disease specific regimens, whether it was paritaprevir/ritonavir/ombitasvir+dasabuvir±ribavirin in ERCHIVES study where only 69% (38/55) of patients with stage 4 − 5 CKD completed therapy, or grazoprevir/elbasvir in the C‐SURFER study where 6/122 patients (4.9%) were excluded from the primary efficacy analysis for non‐virological reasons . The latter were death, loss to follow‐up, non‐compliance, patient withdrawal and withdrawal by physician for violent behaviour.…”
Section: Discussioncontrasting
confidence: 63%
“…In this study, all 24 patients receiving hemodialysis, including 17 with genotype 2, achieved SVR12 without treatment discontinuation. For dialysis‐dependent patients, GLE/PIB would be a promising treatment option, although recent studies of SOF‐based regimens for patients with advanced CKD/dialysis dependence have shown a high virologic effect and a low rate of adverse events related to renal impairment …”
Section: Discussionmentioning
confidence: 99%
“…Among patients infected with HCV genotype 2, the prevalence of subtype 2a was higher than that of subtype 2b, although for approximately 15% the HCV subtype was unknown. Of those with HCV genotype 2, 79.2% (n = 152) were treatment-naïve, 26.0% (n = 50) had diabetes mellitus, 22.9% (n = 44) had cirrhosis, 7.8% (n = 15) had a history of HCC treatment prior to GLE/PIB, and 7.4% (n = 17) were receiving hemodialysis. Of the treatmentexperienced patients, 21 had previously received SOF and ribavirin (RBV).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…We included the data of two patients who previously experienced treatment with SOF + RBV, both of whom achieved SVR12 in retreatment with LDV/SOF. Regarding the use of SOF for patients with renal impairment, recent studies have shown a high virological effect and a low rate of adverse effects, irrespective of the extent of chronic kidney disease (CKD) and whether or not the patient was receiving hemodialysis . Because of the small sample size in the present study, especially for the special populations, such as cirrhosis, CKD, or treatment experience, we were unable to conclusively show the effectiveness of LDV/SOF for HCV GT2 patients.…”
Section: Discussionmentioning
confidence: 59%